If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 + (2y + -2) * yi = 0 Reorder the terms: 2x + 3 + (-2 + 2y) * yi = 0 Reorder the terms for easier multiplication: 2x + 3 + iy(-2 + 2y) = 0 2x + 3 + (-2 * iy + 2y * iy) = 0 2x + 3 + (-2iy + 2iy2) = 0 Reorder the terms: 3 + -2iy + 2iy2 + 2x = 0 Solving 3 + -2iy + 2iy2 + 2x = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -2iy + 2iy2 + -3 + 2x = 0 + -3 Reorder the terms: 3 + -3 + -2iy + 2iy2 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2iy + 2iy2 + 2x = 0 + -3 -2iy + 2iy2 + 2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2iy + 2iy2 + 2x = -3 Add '-2x' to each side of the equation. -2iy + 2iy2 + 2x + -2x = -3 + -2x Combine like terms: 2x + -2x = 0 -2iy + 2iy2 + 0 = -3 + -2x -2iy + 2iy2 = -3 + -2x Reorder the terms: 3 + -2iy + 2iy2 + 2x = -3 + -2x + 3 + 2x Reorder the terms: 3 + -2iy + 2iy2 + 2x = -3 + 3 + -2x + 2x Combine like terms: -3 + 3 = 0 3 + -2iy + 2iy2 + 2x = 0 + -2x + 2x 3 + -2iy + 2iy2 + 2x = -2x + 2x Combine like terms: -2x + 2x = 0 3 + -2iy + 2iy2 + 2x = 0 The solution to this equation could not be determined.
| 20=2w+4 | | 5.2(x-2.25)=-20.4 | | 18=2h-4 | | 54=-9a | | 4z+2=6z | | 12x^2+2x=5 | | 3(4-c)=-4(c-6) | | -8=a/-10 | | 4.375=7/8(b-4) | | -8=s/-10 | | (2a+9)(5a-6)=0 | | -5-4(6+7y)= | | 4x-(-2)-7x+12=5 | | -6x+21.4=2.2 | | 5n=3n+27 | | 100=p/10 | | -(4y+3)-(-3y-7)=1 | | (8h-1)(2h-3)=0 | | 3w+3=5w+7 | | 103.5=9(m+3.7) | | (4n+3)(n+9)=0 | | b+b+b+22=b+b+6 | | 4x+4=-7+2x+25 | | -7(-2-6b)+9b= | | 12p+3=30 | | pie=7.3m | | 2u-10=0 | | 2w+3.7=0.5 | | 13x-34=10x-10 | | (b-7)(b+3)=0 | | 2u-10=14 | | 800=16n^2+56n |